2021
DOI: 10.1111/jvs.13033
|View full text |Cite
|
Sign up to set email alerts
|

Rapid post‐fire re‐assembly of species‐rich bryophyte communities in Afroalpine heathlands

Abstract: Questions In some fire‐prone ecosystems, bryophytes play a crucial role by providing the surface fuel that controls the fire return interval. Afroalpine heathlands are such an ecosystem, yet almost nothing is known about the bryophytes in this system. We do not know the level of species richness, or if there is a successive accumulation of species over time, or if some species are adapted to specific phases along the successional gradient, for example early‐successional species sensitive to competition. Locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
(120 reference statements)
4
5
0
Order By: Relevance
“…Consistent with our findings, Hylander et al. (2021) also found that Funaria hygrometrica was strongly associated with early successional sites. This cosmopolitan species is known to colonise newly disturbed sites around the world, particularly following fires.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our findings, Hylander et al. (2021) also found that Funaria hygrometrica was strongly associated with early successional sites. This cosmopolitan species is known to colonise newly disturbed sites around the world, particularly following fires.…”
Section: Discussionsupporting
confidence: 93%
“…Hylander et al. (2021) found that the richness of bryophytes increased rapidly from 3 to 42 following fire in Afroalpine heathlands in Ethiopia. However, as with our study they also found that the richness levelled off after 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the densities of the most abundant bird species, we found no significant differences between burnt and unburnt areas, ). An increase in species richness with time since fire on burnt areas reflects the dispersal of species and was also described for Afroalpine heathlands (Hylander et al, 2021) and subalpine Rocky Mountain vegetation (Coop et al, 2010). The hump-shaped pattern in our study might be explained by the intermediate disturbance hypothesis (Connell, 1978), as early and late successional species build a common species pool at an intermediate recovery state.…”
Section: Fire Impact On Most Abundant Speciessupporting
confidence: 80%
“…Frost et al, 2020; Tsuyuzaki et al, 2018), very few studies have assessed the impacts of fire on biodiversity at the landscape level. From Afroalpine heathlands, for example, it is known that a fire‐induced landscape mosaic can lead to species rich communities and increase their resilience to warming (Hylander et al, 2021; Johansson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation